Penerapan nilai-nilai pendidikan ekonomi keluarga dalam sektor bisnis UMKM di masa pandemi - Rohmawati Nurlaila; Agung Haryono (Universitas Negeri Malang, 2021)
Economics education of family is part of informal education which is done unprogrammed. Economics education of family is very important to be given to children to make them effective, efficient, and rational human beings in managing finances and utilizing existing resources. The purpose of this study was to determine the values of family economic education through family financial management, provision of pocket money, saving habits and living frugally, child consumption, and entrepreneurial spirit which is applied by families of MSMEs in Rejoso Hamlet, Junrejo Village, Junrejo District, Batu City. This study used a descriptive qualitative approach with a case study research type. The data collection stage includes observation, interviews, and documentation. The result of this research is that family financial management during the pandemic depends on the running business of the family, giving pocket money to children during the pandemic is carried out using a